KEBIJAKAN DESENTRALISASI BIDANG PENDIDIKAN - Dayat Hidayat (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
One aspect that has undergone significant transformation amid the implementation of local autonomy and decentralization is the role and relationship between central and local governments. In the past, central government played a major role in determining the policy of national education. Now, central government focuses more on resolving the national strategic policies. Meanwhile, technical issues on education management become the responisibility of local governments (city andregency).